2017
DOI: 10.17718/tojde.340399
|View full text |Cite
|
Sign up to set email alerts
|

The Motivation Impact of Open Educational Resources Utilization on Physics Learning Using Quipper School App

Abstract: The distribution of the education quality in Indonesia is relatively uneven. This affects the quality of secondary school graduates. On the other hand, the national growth of Information Communication Technology usage in Indonesia is very high, including the use of mobile technology. This is an opportunity for the application of OER (Open Educational Resources) in learning. This study aims to look at the impact of the application of the concept of blended learning OER to motivate students, especially in learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
8
1
3
Order By: Relevance
“…Good motivation encourages students to develop various aspects of learning performance. Various learning strategies are developed by educators and researchers to be able to provide a learning environment that encourages higher motivation [3,4], including achieving mathematics learning outcomes [5,6]. Therefore, researchers are interested in seeing motivation and problem-solving abilities using a guided discovery learning model.…”
Section: Introductionmentioning
confidence: 99%
“…Good motivation encourages students to develop various aspects of learning performance. Various learning strategies are developed by educators and researchers to be able to provide a learning environment that encourages higher motivation [3,4], including achieving mathematics learning outcomes [5,6]. Therefore, researchers are interested in seeing motivation and problem-solving abilities using a guided discovery learning model.…”
Section: Introductionmentioning
confidence: 99%
“…Practicing to use positive words also makes all students feel good peer support. Facilitating useful behavior during learning activities will increase the learning performance (Stolk and Harari, 2014;Sulisworo et al, 2017a) during mobile learning activities.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study concluded that OER can not only help students learn in formal classrooms, but can also help students' self-organized learning. The study (Sulisworo, Sulistyo, & Akhsan, 2017) also aimed to consider the impact of the application of OER on stimulating student learning in one of the high schools in Indonesia, and the study to achieve that goal followed the quasi-experimental approach with two experimental groups of (34) students, and the control that included (27) students, the results concluded that the student satisfaction with learning using OER tends to be similar to traditional face-to-face learning, and the results also indicate the positive impact of OER on stimulating student learning.…”
Section: Literature Reviewmentioning
confidence: 99%